2016
DOI: 10.1111/jfs.12338
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic potential and function of a Lactobacillus strain L1 isolated from Silage

Abstract: One strain L1 was isolated from silage and identified as Lactobacillus rhamnosus confirmed by sequencing of its 16S rDNA genes. The isolate in this study showed sensitive traits to antibiotics, including the clinically relevant antibiotic tetracycline. It showed inhibition against pathogen E. Coli, good adhesion ability to epithelial intestinal cell line LS‐174T and the strong competitive exclusion of E. coli adhesion to LS‐174T (84.1% exclusion). The gastrointestinal transit proved the strain survived well us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…J. Wang, Li, Zhou, Zhang, and Shi (2016) confirmed that the strain of L. rhamnosus L1, isolated from silage, shows sensitivity traits for six antibiotics, including ampicillin, tetracycline, chloramphenicol, ciprofloxacin, and with erythromycin being slightly sensitive to kanamycin, while resistant to VA and MTZ. The resistance of Lactobacillus to VA has been previously reported by Danielsen and Wind (2003).…”
Section: Antibiotics Susceptibility Testsmentioning
confidence: 61%
“…J. Wang, Li, Zhou, Zhang, and Shi (2016) confirmed that the strain of L. rhamnosus L1, isolated from silage, shows sensitivity traits for six antibiotics, including ampicillin, tetracycline, chloramphenicol, ciprofloxacin, and with erythromycin being slightly sensitive to kanamycin, while resistant to VA and MTZ. The resistance of Lactobacillus to VA has been previously reported by Danielsen and Wind (2003).…”
Section: Antibiotics Susceptibility Testsmentioning
confidence: 61%
“…Antimicrobial activity was evaluated based on Shukla and Goyal (2014) and Wang et al (2016). Briefly, the tested pathogenic bacteria (E. coli ATCC 25922, S. aureus ATCC 25923 and S. typhimurium ATCC 14028) were grown in NB medium and LAB was grown in MRS broth at 37 °C for 24 h. Then, the LAB culture was removed by centrifugation at 6000 × g, 4 °C for 10 min.…”
Section: Antimicrobial Activity Assaysmentioning
confidence: 99%